A hierarchical prediction scheme for effective properties of fuzzy fiber reinforced composites with two-scale interphases: Based on three-phase bridging model. (January 2021) - Rao, Yanni; Ban, Jing; Yao, Song; Wang, Kui; Wei, Ning; Lu, Yue; Ahzi, Said
Abstract: In this paper, based on Huang's bridging model (Huang Z-M, 2001), an effective and concise analytical prediction scheme for effective elastic properties of fuzzy fiber reinforced composites' (FFRCs), is presented. The distinctive constructional feature of the FFRCs, herein, is that the fuzzy fibers are continuous, aligned, and having wavy nanofillers (like CNTs) grown radially on the circumferential surfaces. By means of the proposed approach, two-scale interphase effects on the overall properties of FFRCs are investigated, including the CNTs/matrix interphase and the fuzzy interphase surrounding the micro-fibers. Meanwhile, the size effect and the waviness effect of nanofillers are evaluated. The accuracy and effectiveness of this prediction scheme is validated by comparisons with the existing experimental data and analytical results. A thorough parametric study indicates that the introduction of slender nanofillers into the micro-fiber/matrix interfacial zone, indeed, leads to significant enhancement to the transverse and shear performance of the composite. Moreover, such enhancement depends on some major parameters, including the contents of the two-scale reinforcements, the stiffness of the two-scale interphase, CNT waviness, as well as the radius and length of CNTs. Those findings may have important implications in the future design of FFRCs. Highlights: An efficient hierarchical prediction scheme is employed for FFRCs' properties. Two-scale interphase effect on FFRCs' effective properties are evaluated. The nano-interphase plays a crucial role in the effective properties of FFRCs. CNTs waviness affects their reinforcement to FFRCs to a certain degree.